Hybrid Picking Applied to Classical Guitar (Per Musi, 2018)
Hybrid picking refers to the practice of using the pick, held between the thumb and index fingers, in a combined action with right-hand medium, ring and pinky fingers. This enables the performance of rhythmic-harmonic accompaniment, as well as polyphonic textures and melodic lines. This work presents the contextualization of this technique applied to classical guitar by discussing historical aspects and indicating musical examples of various genres and composers. For those guitarists who use the pick exclusively, hybrid picking allows the performance of a mostly varied repertoire.